2021
DOI: 10.1101/2021.11.16.468918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic analysis of liver tissue revealsAeromonas hydrophilainfection mediated modulation of host metabolic pathways inLabeo rohita

Abstract: Aeromonas hydrophila (Ah) is an opportunistic Gram-negative bacterium and a serious global pathogen causing Motile Aeromonas Septicaemia (MAS) in fish and many other vertebrates. The pathogenesis of aeromonas septicaemia is complex and involves multiple perturbed pathways. Molecular analysis of host tissues could be a powerful approach to identify mechanistic and diagnostic immune signatures of disease. We performed a deep proteomic analysis of Labeo rohita liver tissue to examine changes in the host proteome … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Different from CYP2AA1 and CYP2AA2 showing the highest expression level in intestine and kidney tissue of zebrafish, respectively (Saad et al, 2016), Ca‐CYP2AA12 mRNA is highly abundant in the head kidney, which may result in the different CYP2AA allele playing a role in different tissue. Compared with other CYP families, Ca‐CYP2F2 may involve in xenobiotics metabolism in many tissues with its mRNA widely and highly expressed in most tissues, which has been demonstrated in liver of Labeo rohita during Aeromonas hydrophila infection (Nissa et al, 2021). Several studies have demonstrated that CYP2J subfamily exhibits diverse members and overlapping expression in different organs (Kikuta et al, 1991; Zhang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Different from CYP2AA1 and CYP2AA2 showing the highest expression level in intestine and kidney tissue of zebrafish, respectively (Saad et al, 2016), Ca‐CYP2AA12 mRNA is highly abundant in the head kidney, which may result in the different CYP2AA allele playing a role in different tissue. Compared with other CYP families, Ca‐CYP2F2 may involve in xenobiotics metabolism in many tissues with its mRNA widely and highly expressed in most tissues, which has been demonstrated in liver of Labeo rohita during Aeromonas hydrophila infection (Nissa et al, 2021). Several studies have demonstrated that CYP2J subfamily exhibits diverse members and overlapping expression in different organs (Kikuta et al, 1991; Zhang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%